2000
DOI: 10.1678/rheology.28.137
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Interfacial Tension between Polymer Liquids : Pendant Drop, Improved Imbedded Fiber Retraction and Steady Shear Flow Methods

Abstract: The interfacial tension between a poly (isobutylene) (PIB) and a poly (dimethylsiloxane) (PDMS) was obtained by an improved imbedded fiber retraction method from the observation of the PDMS (or PIB) droplet shape in the PIB (or PDMS) matrix after application of the step shear strain. The interfacial tension was also obtained from the observation of the PDMS (or PIB) droplet shape during the steady shear flow. We compared the values of interfacial tension obtained by these methods with the value determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…This improved method of imbedded fiber retraction was applied to polystyrene/poly(methyl methacrylate) melt systems 4) and to PIB/PDMS systems. 6) It was shown that the improved method gives comparable value of interfacial tension with those obtained by the breaking thread and pendant drop methods.…”
Section: Introductionmentioning
confidence: 94%
“…This improved method of imbedded fiber retraction was applied to polystyrene/poly(methyl methacrylate) melt systems 4) and to PIB/PDMS systems. 6) It was shown that the improved method gives comparable value of interfacial tension with those obtained by the breaking thread and pendant drop methods.…”
Section: Introductionmentioning
confidence: 94%
“…1) Elmendorp and de Vos 2 ) used the spinning drop method and Elemans 3) et al used the breaking thread method. Recently, the imbedded fiber retraction (IFR) method was used [4][5][6] and other methods have been introduced which are using the shear oscillation test. [7][8][9][10] When the interfacial tension was measured, the dynamic modulus can be predicted by the emulsion model.…”
Section: Introductionmentioning
confidence: 99%
“…と変化する.界面のエネルギーが界面積に比例することを考 えれば,この形状変化は界面積の減少と対応する. 18,19) 配向角 θは,アフィン変形で与えられる角度 に等しく,形状回復の間一定に保たれることを見出した. 18,19) マトリックスの粘度が比較的高く,観測しやすいように液滴 のサイズを大きくしているため,回転緩和の時間が非常に長 くなり,観測時間の間では θが一定であるように見えるので ある. 18,19) ダンベル形状の出現に関して,当時は無限の長さの 棒状界面に現れるRayleighの不安定性の波の一部が見えてい るものと思っていた. 19) ダンベル中央のくびれ部の包絡線が コサイン波で表されるので 18,19) 安心していた.しかし,棒状 からダンベル状への比較的短い時間の間にこのRayleigh波が 成長することはできないことを最近見出した. 20) ダンベル形 状の出現は,有限の長さの棒状界面の両端に現れる球根状の end-pinchingがその原因であることを示唆した. 20) 伸長した長軸a の収縮に伴う界面積Sの減少の実験結果を Fig. 2に示す. 19) 方法を提案した. 17) また,この新しい方法が,ブレーキング・ スレッド法(界面のRayleigh不安定性から界面張力を求める 方法)と同等の実験結果が得られることを示した. 17) さらに Hayashiらは,この繊維収縮法をPIB/PDMSの系に適用し,標 準的なペンダントドロップ法と同等の実験結果を得た. 22) 2.2.3 液滴の長軸・短軸の時間変化の予測 収縮過程にある軸対称の液滴に働く回復力と粘性抵抗力 のバランスは次式で表される. 23) ここで,tは時間,L (= 2a) 一方,HPC25 %/PDMS 20/80(wt/wt) ブレンドでは,フルオレ セインをHPC25 % に微量加え,偏光顕微鏡で液滴サイズの分 布を測定した.Pre-shear後のr V /r N の値は1.93で,液滴相のサ イズ分布はかなり広い.分布がある場合でも,Fig. 6が液滴サ イズによらない換算形であることを利用して,スケーリング が次のように行える.まず,単一液滴の∆ G(t,γ) が,r 0 によら ないユニバーサルな関数Fを用いて次のように表せる. Fig.…”
unclassified